2012
DOI: 10.4238/2012.february.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid protocol for the isolation of PCR-amplifiable DNA from medicinal plants

Abstract: ABSTRACT.Medicinal plant species has a valuable economic importance because of its usage as pharmaceuticals, nutritional, as well as its use in popular medication. For DNA-based techniques, nanogram quantities of the purified DNA are requisite to amplify and yield sufficient amounts of PCR products. SDS-based DNA isolation method was used to extract DNA from 11 species of different aromatic and medicinal plants collected from Saudi Arabia. Three hundred milligrams of fresh shredded plant material was necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These studies successfully demonstrated the use of SSR alleles to distinguish between large numbers of date palm cultivars. Alatar et al (2012) detected polymorphism in different medicinal plant species in Saudi Arabia and provided a protocol for DNA isolation and the SSR-PCR method. A microsatellite-based investigation of gene flow between wild barley Hordeum spontaneum and cultivated barley Hordeum vulgare was also performed by Hubner et al (2012) in Jordan.…”
Section: Standard Molecular and Genomic Techniques In Plant Biodiversmentioning
confidence: 99%
“…These studies successfully demonstrated the use of SSR alleles to distinguish between large numbers of date palm cultivars. Alatar et al (2012) detected polymorphism in different medicinal plant species in Saudi Arabia and provided a protocol for DNA isolation and the SSR-PCR method. A microsatellite-based investigation of gene flow between wild barley Hordeum spontaneum and cultivated barley Hordeum vulgare was also performed by Hubner et al (2012) in Jordan.…”
Section: Standard Molecular and Genomic Techniques In Plant Biodiversmentioning
confidence: 99%
“…Liquid nitrogen or dry ice is required for grinding in most traditional plant gDNA extraction methods (Dellaporta et al, 1983;Mohd-Hairul et al, 2011;Alatar et al, 2012;Mornkham et al, 2012;Souza et al, 2012). However, liquid nitrogen or dry ice cannot be obtained quickly in remote locations, especially in many developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Most conventional gDNA extraction methods are based on a 1.5-or 2.0-mL microcentrifuge tube format (Moslem et al, 2010;Mohd-Hairul et al, 2011;Alatar et al, 2012;Mornkham et al, 2012;Ojeda et al, 2012;Souza et al, 2012). Although it is effective in lowthroughput applications, these methods are inconvenient for a large number of samples.…”
Section: Introductionmentioning
confidence: 99%